2018
DOI: 10.1101/402800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GI-16 lineage (624/I or Q1), there and Back Again: the history of one of the major threat for poultry farming of our era

Abstract: 26 The genetic variability of Infectious bronchitis virus (IBV) is one of the main challenges for its 27 control, hindering not only the development of effective vaccination strategies but also its 28 classification and, consequently, epidemiology understanding. The 624/I and Q1 genotypes, now 29 recognized to be part of the GI-16 lineage, represent an excellent example of the practical 30 consequences of IBV molecular epidemiology limited knowledge. In fact, being their common 31 origin unrecognized for a lon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…However, a small Asian clade stemming from the European one was present (Supplementary Figure S1). While not directly relevant to the purpose of this study, this finding may reflect a previously observed pattern for IBV lineage GI-16 (Q1) [39], and its epidemiological implications and potential developments should be considered and monitored.…”
Section: Discussionmentioning
confidence: 67%
“…However, a small Asian clade stemming from the European one was present (Supplementary Figure S1). While not directly relevant to the purpose of this study, this finding may reflect a previously observed pattern for IBV lineage GI-16 (Q1) [39], and its epidemiological implications and potential developments should be considered and monitored.…”
Section: Discussionmentioning
confidence: 67%
“…While North America was the main nucleus of viral dispersal, other significant contacts among areas were reported and these reflected previously described patterns for other avian infectious diseases and/or mirrored well-established economic and commercial relationships among areas. The bidirectional flow of viral strains involving Asia and Europe was already reported for IBV [53,54], as well as the "mediator role" played by the Middle East in this migratory path [55]. Similarly, different areas were involved in ARVs' introduction to Africa, reflecting the changing economic relationships and interests of different areas of the world with different countries of this continent.…”
Section: Discussionmentioning
confidence: 71%
“…Although these intrinsic methodological and data limitations can prevent the accurate reconstruction of the ancient virus origin, a reliable depiction of recent patterns could be reached. The viral population was featured by a progressive rise and high-level circulation until about the 2000s, a pattern shared by many other livestock pathogens [50][51][52][53]. This mirrors the progressive intensification of farming that, in turn, led to an increase in animal densities, movements and trades, creating favorable conditions for viral population expansion [51,53,54].…”
Section: Discussionmentioning
confidence: 99%